Utviklingen av fysiske ferdigheter og arrestasjonsteknikk i det norske politiet - Pål Lagestad (Nordisk Politiforskning, 2015)
The main objective of this study was to examine the frequency of police officers’ training and use of arresting techniques and to investigate police officers’ attitudes to annual physical tests of physical skills and arresting techniques. The study also examines the officers’ assessment of their own physical skills. The results show that most of the police officers rarely use arresting techniques during police work, and only train arresting techniques two to five times a year. It is argued that this is insufficient to maintain and develop adequate skills. However, the results also show that the police officers are in general positive to annual physical tests of physical skills and arresting techniques – a strategy that may increase the training frequency. Finally, the police officers assessed their own physical skills as being at the same level after three years in the job.